The Hopeful Minds Programme: A Mixed-method Evaluation of 10 School Curriculum Based, Theoretically Framed, Lessons to Promote Mental Health and Coping Skills in 8–14-year-olds. Issue 2 (3rd April 2021) - Kirby, K.; Lyons, A.; Mallett, J.; Goetzke, K.; Dunne, M.; Gibbons, W.; Ní Chnáimhsí, Á.; Ferguson, J.; Harkin, T. W.; McGlinchey, E.; McAnee, G.; Belfar, M. L.; et al.
ABSTRACT: This study is the first evaluation of Hopeful Minds: a novel school-based mental health promotion programme designed for children and pre-adolescents. Ten hope theory-based lessons were assessed. A mixed-methodology design was used with a sample of 127 participants (88 pre/post; 39 focus groups), aged 8–13 years. In the pre/post-study, there were significant improvements in anxiety and emotional regulation levels (primary school), coping and resilience levels (post-primary). Focus groups were conducted with three post-primary groups. The key overarching qualitative themes included developing a hopeful mind; increased emotional insight and awareness; improved resilience, confidence, self-belief, and developing new coping skills and a request to provide the programme to all transitioning primary school children. Outcomes provide preliminary evidence indicating that the Hopeful Minds programme, which utilises 'Hope theory' as it's foundation, has potential in preventing the development of mental health issues in pre and early adolescent children. Recommendations include adopting a whole school approach, include additional lessons on rumination and academic failure.